SOMEONE TO LISTEN: INCREASING YOUTH HELP‐SEEKING BEHAVIOR THROUGH A TEXT‐BASED CRISIS LINE FOR YOUTH. Issue 4 (21st March 2013) - Evans, William P.; Davidson, Laura; Sicafuse, Lorie
<x xml:space="preserve">Abstract</x> A multi‐method evaluation was conducted to assess the TextToday pilot program, the nation's first crisis line with the capacity to accept text messages. Objectives of the evaluation included how successful the system was in meeting the needs of underserved youth and how effectively the social marketing campaign reached the target population with information about the texting crisis service. The service was found to increase youth help‐seeking behaviors among our pilot study population. Implications for replication, integrating texting into community crisis services, and future research are discussed.